Parents' Perceptions of Zoning-Based Elementary School Admissions: A Structured Literature Review - Nabila Nur Fitria; cantika sri agustin; Thalytha Majma Tsaqifa Taftazani; Annisa Siti Aisyah; Sofyan Iskandar (Jurnal Penelitian, 2026)
The zoning-based Student Admission Policy (Penerimaan Peserta Didik Baru, PPDB) was introduced to improve geographical access and reduce inequalities among Indonesian schools, yet its implementation has generated mixed responses from parents. This structured qualitative literature review examines parental perceptions, satisfaction and objections, and the effects of zoning on elementary-school choice. The analytical corpus comprised 15 topic-specific scholarly publications issued between 2019 and 2025, supplemented by two official policy and international education reports. Sources were identified through Google Scholar, SINTA, relevant publisher platforms, and official education websites using Indonesian and English search terms. Publications were included when they addressed school admissions, parental perceptions, implementation quality, school choice, or educational equity at the elementary or compulsory-education level. Data were synthesized through deductive-inductive thematic coding. Four themes emerged: perceived benefits of proximity and equitable access; restrictions on parental choice; implementation quality, information, and technical barriers; and contextual inequalities in school quality and family resources. The review's novelty lies in integrating parental perception, public-service satisfaction, and educational-equity perspectives into one conceptual model. The findings indicate that zoning is more likely to receive parental support when school quality is relatively even, procedures are transparent, and families receive accessible and personalized information. Conversely, unequal school quality and weak implementation can convert a formally equitable policy into a source of distrust and strategic behavior. The review contributes a policy-oriented framework for improving communication, complaint handling, digital registration, and quality equalization across schools.